Hazard Identification, Risk Assessment, Risk Control (HIRARC) pada PT Jindal Stainless Indonesia - Bima Wiyogo Oetoyo; Kriswanto Widiawan (Jurnal Titra, 2022)
The company needs an update on the HIRARC document because after conducting the audit, the company needs an update. The method to be used is Hazard Identification, Risk Assessment, Risk  Control (HIRARC) for further identification, assessment, and control. HIRARC is a method used to find out what are the potential hazards and risks that can occur in an activity or activity, after knowing the potential hazards and risks, a risk assessment will be carried out to determine the level at which the potential hazards and risks are located. Risk control is a way to reduce the value of risk by means of elimination, substitution, mechanical engineering and administration, and the use of PPE in accordance with the risk control hierarchy. In the stainless production area, there are 9 machines used for the production process with the initial assessment results of 38 sub-activities in the low risk category, 18 sub-activities in the moderate risk category, 9 sub-activities in the high risk category, and 1 sub-activity in the extreme risk category. The estimated value after controlling becomes 60 sub-activities in the low risk category, 3 sub-activities in the moderate risk category, and 3 sub-activities in the high risk category.